Eidophelus caucasicus (Lindemann, 1877) a bark beetle confirmed for the Italian fauna after almost 100 years (Coleoptera: Curculionidae, Scolytinae) - Dal Cortivo, Marialuisa (Fragmenta entomologica, 2024)
A monitoring project focused on saproxylic beetles of “Sasso Fratino Integral Nature Reserve” (Bagno di Romagna, FC), allowed to confirm the presence of the bark beetle Eidophelus caucasicus (Lindemann, 1877) for the Italian fauna. This species was previously known only for “Venezia Tridentina” (corresponding to the current Trentino-South Tyrol) from an old record, never confirmed for Italy since.